Some Aspects of Ensuring Access to Health Care in Moscow Polyclinics - Z. Kh. Agamov; O. A. Zernova; A. Ye. Yakubova; M. M. Dzagoev; R. G. Zulkarnaev; V. V. Prichepa; M. N. Alimuradov; A. L. Koshkakaryan (Здоровье мегаполиса, 2025)
Background. Ensuring access to health care is a priority area of development in Russian healthcare. Introducing new organizational technologies along with eliminating medical staff shortages is important to improve access to health care. Doctors provide care at consultations, so they are the polyclinic’s most valuable resource. Therefore, doctors' working time is lost and access to health care is limited when patients fail to show up without canceling an appointment. Purpose. To ensure access to health care by eliminating the loss of doctors' working time due to patient no-shows. Materials. The authors used the results of a facility-based experiment and the data from the Unified Medical Information System (EMIAS) on the number of people who made an appointment with doctors of various specialties at a city polyclinic during one calendar year and the number of people who did not show up for an appointment later. Methods. The authors carried out a facility-based experiment and applied analytical, sociological, and statistical methods. Results. The percentage of people who pre-registered to an appointment with a doctor but subsequently failed to show up for it at a Moscow polyclinic ranged from 9% to 18.9%, depending on the medical specialty. During a facility-based experiment, the nurses of an urology office called patients who had made an appointment with a urologist to confirm their attendance. The experiment enabled to reduce the proportion of missed appointments from 13 to 3.4% (p < 0.001). Conclusion. Preliminary communication between patients who have made an appointment with doctors, and polyclinic’s healthcare workers who call patients to remind them about appointments and receive their confirmation or refusal to show up for an appointment is proved to be efficient to ensure access to health care in Moscow polyclinics.